Military Medical Research - Fu, Xiao-Bing; Fu, Xiao-Bing
Military Medical Research is an open access, peer-reviewed journal publishing cutting-edge findings on basic medical science and clinical research that is related to military medicine. The journal aims to translate the basic science research into the clinical practice and combine advances in civilian and military medicine, with a special focus on the modern military medicine disciplines and the leading progress in precision medicine and translational medicine. Military Medical Research considers articles mainly related to the fields of trauma and war surgery, disaster medicine, emergency medicine and critical care, infectious diseases and military psychiatry/psychology. Topics of interest in Military Medical Research may also include, but are not limited to the following: CBRN (chemical, biological, radiological, nuclear) medical countermeasures, mass casualty readiness and response, environmental medicine (including austere environments such as battlefields, high altitude, extreme cold and hot environments), aerospace medicine and marine medicine, and military training as well as health service.